Carbohydrates do not accelerate force recovery after glycogen-depleting followed by high-intensity exercise in humans - Cheng, A. J.; Chaillou, T.; Kamandulis, S.; Subocius, A.; Westerblad, H.; Brazaitis, B.; Venckunas, T. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Prolonged low-frequency force depression (PLFFD) induced by fatiguing exercise is characterized by a persistent depression in submaximal contractile force during the recovery period. Muscle glycogen depletion is known to limit physical performance during prolonged low- and moderate-intensity exercise, and accelerating glycogen re-synthesis with post-exercise carbohydrate intake can facilitate recovery and improve repeated bout exercise performance. Short-term, high-intensity exercise however, can cause PLFFD without any marked decrease in glycogen. Here we studied whether recovery from PLFFD was accelerated by carbohydrate ingestion after 60-min of moderate-intensity glycogen-depleting cycling exercise followed by six 30-s all-out cycling sprints. We used a randomized cross-over study design where nine recreationally-active males drank a beverage containing either carbohydrate or placebo after exercise. Blood glucose and muscle glycogen concentrations were determined at baseline, immediately post-exercise, and during the 3-h recovery period. Transcutaneous electrical stimulation of the quadriceps muscle was performed to determine the extent of PLFFD by eliciting low-frequency (20Hz) and high-frequency (100Hz) stimulations. Muscle glycogen was severely depleted after exercise, with a significantly higher rate of muscle glycogen re-synthesis during the 3-h recovery period in the carbohydrate than in the placebo trials (13.7 and 5.4 mmol glucosyl units/kg wet weight/h, respectively). Torque at 20Hz was significantly more depressed than 100 Hz torque during the recovery period in both conditions, and the extent of PLFFD (20/100Hz ratio) was not different between the two trials. In conclusion, carbohydrate supplementation enhances glycogen re-synthesis after glycogen-depleting exercise but does not improve force recovery when the exercise also involves all-out cycling sprints.